A contação de histórias como ferramenta pedagógica para construção de uma educação antirracista desde a infância - Pacheco, Jefferson Duarte (2022)
This research aims to analyze how much the Afrocentric storytelling can contribute to the construction of an anti-racist education from the childhood. For the theoretical basis of the research, we list the concepts that involve memory, performance and orality. As for memory, we dialogue with the studies of Paul Ricoeur (2007); about performance and orality, with the reflections of Paul Zumthor (2007); in terms of storytelling, oral tradition and the figure of the Griot, with Hampátê Bá (2010); regarding questions about ethnic-racial relations and racial education in childhood education, with Cavalleiro (2003). Through a participatory research, which involved the telling of the story Zacimba Gaba: the warrior princess for kindergarten children, we’ve formed round talks which favored the construction of a dialogic practice and it enabled the exercise of collective thinking. Our study contributes to other possibilities of reading and perceptions about storytelling to children, providing the construction ofa playful and affectionate environment to treat complex issues of society, such as: racism, discrimination and racial prejudice since childhood. In this way, storytelling also gains a character didactic, important for the construction of an anti-racist education that values the traditions, territories and ancestral knowledge already in Early Childhood Education.